Playing games in the forest: state-local conflicts of land appropriation - Angelsen, A. (2001)
This paper explores possible strategic interactions between the state and local community in games of tropical forest land appropriation. Three typical cases are discussed, corresponding to a development over time of increased resource competition and market integration. The local response to more state deforestation depends on the costs, market, and behavioral assumptions, and less on the structure of the game (Cournot or Stackelberg). The state fuels local deforestation by providing infrastructure (roads) which reduces the net costs of agricultural expansion, or when markets are imperfect and local behavior determined by survival needs. The game structure is, however, important for total deforestation.